Atypical carcinoid of the primary kidney with retroperitoneal metastasis 15 years later: A case report and literature review - Qiang Wang; Dong Zhuo; Houbao Huang; Jianping Tao (Urology Case Reports)
Primary renal neuroendocrine tumors (NETs) are extremely rare among renal malignancies. According to pathological manifestations, carcinoid can be divided into four types: typical carcinoid, atypical carcinoid, large cell and small cell neuroendocrine carcinoma. Primary or secondary retroperitoneal carcinoid is even rarer than renal carcinoid. This article reports a patient with renal carcinoid complicated with retroperitoneal metastasis, who developed retroperitoneal metastasis 15 years after radical nephrectomy. Through the analysis of this case and the combination of the existing published literature, it is aimed to provide valuable references for clinicians in treating patients with renal carcinoid or with metastasis.